Jonathan Abernathy you are kind : a novel - McGhee, Molly, 1994- (Astra House, 2023)
"A piercing critique of late stage capitalism and a reckoning with its true cost, JONATHAN ABERNATHY YOU ARE KIND is about a man who takes a job as a dream auditor to pay off an insurmountable student loan debt"--